(untitled) (Semiárida, 2024)
This study provides a brief description of the flora of Cuchillo Curá Nature Reserve. It includes a list of species and their status (native, exotic, endemic). It is the result of botanical explorations done in spring of 2018, 2022 and 2023. We photographed and collected specimens for taxonomic determination. One hundred and sixteen vascular plants were identified, mainly native taxa, including five endemic species and one new record for Neuquén. Most species belong to the Occidental district of the Patagonian phytogeographic province, but the presence of elements unique to Payunia and Monte indicates a transitional area between these floral units. Asteraceae and Poaceae were the most represented families. This knowledge contributes to biological conservation guidelines and future management strategies in the reserve.